Inadequate left ventricular unloading during ramp is associated with hospitalization or death during left ventricular assist device support. Issue 2 (3rd September 2020) - Rosenbaum, Andrew N.; Stulak, John M.; Clavell, Alfredo L.; Behfar, Atta
Abstract: A combined right and left‐sided heart catheterization (RHC/LHC) protocol was recently reported to optimize patients supported by left ventricular assist device (LVAD). Using this platform, we sought to evaluate the prognostic significance of several hemodynamic indices, including left ventricular end‐diastolic pressure (LVEDP) and transaortic gradient (peak aortic pressure ‐ peak left ventricular pressure in systole, TAG). We evaluated all patients undergoing RHC/LHC at our institution from 2015 through 2018, and comprehensive clinical data were obtained. Primary end points were (1) a composite outcome that included hospitalization or death and (2) 1‐year overall survival after catheterization. Forty‐two patients were included in the analysis. Optimization resulted in normalization of hemodynamic parameters; all variables were significantly improved from baseline ( P  ≤ .05). On univariate modeling, final LVEDP was associated with the primary end point (hazard ratio [HR], 1.2 per 1‐mm Hg increase; 95% CI, 1.1‐1.3; P  = .002). After adjusting for LVAD speed, TAG, and cardiac index in a multivariate model, the association between LVEDP and the composite end point remained significant (HR, 1.2 per 1‐mm Hg increase; 95% CI, 1.1‐1.4; P  = .001). In the setting of LVAD support, inadequate LV unloading was a significant marker of poor outcomes with time, suggesting that LVEDP is a central prognostic marker in this population.